First-Order Adaptive Azimuthal Null-Steering for the Suppression of Two Directional Interferers. (9th February 2010) - Derkx Derkx, René M. M. René M. M.
Abstract : An azimuth steerable first-order superdirectional microphone response can be constructed by a linear combination of three eigenbeams: a monopole and two orthogonal dipoles. Although the response of a (rotation symmetric) first-order response can only exhibit a single null, we will look at a slice through this beampattern lying in the azimuthal plane. In this way, we can define maximally two nulls in the azimuthal plane which are symmetric with respect to the main-lobe axis. By placing these two nulls on maximally two directional sources to be rejected and compensating for the drop in level for the desired direction, we can effectively reject these directional sources without attenuating the desired source. We present an adaptive null-steering scheme for adjusting the beampattern so as to obtain this suppression of the two directional interferers automatically. Closed-form expressions for this optimal null-steering are derived, enabling the computation of the azimuthal angles of the interferers. It is shown that the proposed technique has a good directivity index when the angular difference between the desired source and each directional interferer is at least 90 degrees.